FAKTOR - FAKTOR YANG MEMPENGARUHI PENGIMPLEMENTASIAN KARTU KREDIT PEMERINTAH: KOMPETENSI SDM SEBAGAI VARIABEL PEMODERASI - Rahmat Taufik, (2023)
The Government Credit Card (KKP) is a payment instrument using a card that can be used to make payments for expenditures that can be charged to the State Budget, where the cardholder's payment obligations are met in advance by the government credit card issuing bank, and the work unit is obliged to pay off payment obligations on time agreed with the payment at once. However, from the start, the adoption of government policies related to non-cash payment systems using KKP has not been optimal. This research is centered on one of the Ministries/Institutions in Indonesia, namely the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in which there are 143 work units that use KKP in their financial processes. This research tries to bridge these policies' lack of optimal implementation by examining the factors that influence user intention to use KKP within the Kemendikbudristek. The purpose of this study is to test the influence of perceived usefulness, perceived ease of use, and facilitating conditions with human resource competence as a moderating variable. The sample in this study was 411 civil servants within Kemendikbudristek who had positions as PPK, BP, and BPP. The data was obtained from the results of the analysis using the Structural Equation Model (SEM) PLS version 3.0. The results showed that perceived usefulness, perceived ease of use, and facilitating conditions significantly influenced the intention to use KKP. As for the moderating variable, human resource competence, it can only moderate the variable perceived ease of use on intention to use KKP.